Targeted genomic analysis of Müllerian adenosarcoma2. Issue 1 (18th November 2014) - Howitt, Brooke E; Sholl, Lynette M; Dal Cin, P; Jia, Yonghui; Yuan, Liping; MacConaill, Laura; Lindeman, Neal; Kuo, Frank; Garcia, Elizabeth; Nucci, Marisa R; Quade, Bradley J
Abstract Müllerian adenosarcoma (MA) is a rare mixed mesenchymal tumour of the female genital tract, composed of malignant stroma and benign‐appearing epithelium. Sarcomatous overgrowth (SO) is the only established histological variable associated with higher stage and shorter survival. Specific molecular or immunohistochemistry (IHC) tools for the diagnosis of MA are lacking. Our goal was to study genomic mutations and copy number variations (CNVs) in MA to understand better its pathobiology, and develop specific diagnostic and prognostic tools. DNA was extracted from 20 samples of MA from 18 subjects (12 without SO and 6 with SO), including two in which areas of both typical MA histology and SO were independently tested. Samples were analysed using a targeted next‐generation sequencing assay interrogating exonic sequences of 275 cancer genes for mutations and CNVs as well as 91 introns across 30 genes for cancer‐associated rearrangements. The mean number of mutations in MA with SO (mean 9.7; range 3–14) did not differ significantly from that in MA without SO (mean 9.6; range 5–16). MA with SO had significantly higher mean numbers of gene‐level CNVs (24.6) compared to MA without SO (5; p = 0.0002). The most frequent amplification involved MDM2 and CDK4 (5/18; 28%), accompanied by focal CDK4 and MDM2 and diffuse HMGA2 expression using immunohistochemistry. MYBL1 amplification was seen in 4/18 (22%), predominantly in SO. Alterations in PIK3CA/AKT/PTEN pathway members were seen in 13/18 (72%). Notably, TP53 mutations were uncommon, present in only two cases with SO. Three out of 18 (17%) had mutations in ATRX, all associated with SO. No chromosomal rearrangements were identified. We have identified a number of recurrent genomic alterations in MA, including some associated with SO. Although further investigation of these findings is needed, confirmation of one or more may lead to new mechanistic insights and novel markers for this often difficult‐to‐diagnose tumour. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd